2016
DOI: 10.1253/circj.cj-16-0663
|View full text |Cite
|
Sign up to set email alerts
|

Protective Roles of Adipocytokines and Myokines in Cardiovascular Disease

Abstract: Obesity is a major risk factor for progression of cardiovascular disease. Adipose tissue is recognized as an endocrine organ producing various secretory molecules, also known as adipocytokines, and dysregulated production of adipocytokines participates in the pathogenesis of obesity complications, including metabolic dysfunction and cardiovascular disorders. Recent evidence indicates that skeletal muscle also functions as an endocrine organ capable of secreting a number of bioactive substances, also referred t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 81 publications
(87 reference statements)
0
25
0
Order By: Relevance
“…The indirect effect is mediated by a myokine targeting an organ involved in metabolic functions [e.g., adipose tissue (AT), pancreas, liver] which (dys)functioning can affect cardiovascular function. However, myokines are often able to act through both ways (8). For instance, follistatin-like 1 (FSTL1) is induced, in both SKM and cardiac muscle, by ischemia and hypertrophic response and it has beneficial effects on vasculature (by limiting EC apoptosis, VSMC proliferation, and neointimal formation) and heart (by limiting cardiac ischemic injury, adverse cardiac remodeling, and cardiac rupture) (8,9).…”
Section: Overview Of Myokines With Cardiovascular Functionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The indirect effect is mediated by a myokine targeting an organ involved in metabolic functions [e.g., adipose tissue (AT), pancreas, liver] which (dys)functioning can affect cardiovascular function. However, myokines are often able to act through both ways (8). For instance, follistatin-like 1 (FSTL1) is induced, in both SKM and cardiac muscle, by ischemia and hypertrophic response and it has beneficial effects on vasculature (by limiting EC apoptosis, VSMC proliferation, and neointimal formation) and heart (by limiting cardiac ischemic injury, adverse cardiac remodeling, and cardiac rupture) (8,9).…”
Section: Overview Of Myokines With Cardiovascular Functionsmentioning
confidence: 99%
“…However, myokines are often able to act through both ways (8). For instance, follistatin-like 1 (FSTL1) is induced, in both SKM and cardiac muscle, by ischemia and hypertrophic response and it has beneficial effects on vasculature (by limiting EC apoptosis, VSMC proliferation, and neointimal formation) and heart (by limiting cardiac ischemic injury, adverse cardiac remodeling, and cardiac rupture) (8,9). On the contrary, irisin induces white-to-brown transition of AT, increasing lipid oxidation-to-storage balance and improving the metabolic profile, finally improving cardiovascular function (10).…”
Section: Overview Of Myokines With Cardiovascular Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A range of myokines, hormones secreted by skeletal muscles during physical activity, have been identified; these include myostatin or brainderived neurotrophic factor (BDNF) (1,2). It has been postulated that low myokine levels play a role in metabolic dysfunction and cardiovascular disorders (3,4).…”
mentioning
confidence: 99%
“…Myostatin, a transforming growth factor-β superfamily protein, regulates myoblast proliferation and is upregulated in cardiomyocytes surrounding infarct areas after myocardial infarction (5,6). Studies have shown that BDNF, which belongs to the neurotropin family, is expressed in nonneurogenic tissues, including skeletal muscles (2), and it regulates glucose metabolism in diabetic mice (7). However, recent research has focused on irisin, a newly identified myokine.…”
mentioning
confidence: 99%